The art of tarannum in quran recitation case study: surah ad-dhuha / Yazrin Azrina Yunus - Yunus, Yazrin Azrina (2011)
With the advancement of technology in communication as well as development of music from years to years, people especially Muslims are lack of knowledge in Islamic sounds art or also known as handasah al-sawt. Majority of them are only listened to the popular music, and not many have interested into Islamic wonderful sounds of art. Sadly, only a part group of audiences have interest to listen and to appreciate this sounds art including tarannum, a technique to recite Quran in melodious way using Arabic modes called maqam, is considered alien to many people even Muslims. Tarannum, is one of the most significant techniques to recite surah in Quran. In order to give information and to recognize the musicality texture in Quran recitation, I have conducted this research study through extensive readings on tarannum and also the art of sounds in Islam. In addition, I also make an analysis of tarannum techniques using musicality terms and characteristics through transcriptions of one of the surah in Quran. For my case study, I had focused on a Surah AD-Dhuha. The findings of this research showed the basic elements in tarannum and the techniques in Quran recitation. Although there are elements of music found in the analysis, the Quran recitation strictly cannot be called music.